2021
DOI: 10.3390/w13223237
|View full text |Cite
|
Sign up to set email alerts
|

Dry-Season Fog Water Utilization by Epiphytes in a Subtropical Montane Cloud Forest of Southwest China

Abstract: Fog water is generally considered to be an important water source for epiphytes in cloud forests because they cannot directly access ground-level water sources. However, the water use proportions of potential water sources and water use efficiency of epiphytes in the subtropical montane cloud forests (MCF) remain to be further explored. In this study, we investigated the water use pattern in the dry season and the intrinsic water use efficiency (WUEi) of four epiphyte groups (i.e., epiphytic lichens, epiphytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Epiphytes' reliance on different water sources seems to be linked to their taxonomic affiliation; Liu et al . (2021) found that in a Chinese subtropical montane forest, bryophytes and ferns obtained water both from humus and fog, whereas lichens and seed plants relied almost exclusively on fog. Although significant tolerance to desiccation (Bader et al ., 2013) and temperature rise (up to an average of 3 °C) has been observed for some epiphytic species (Müller, Albach & Zotz, 2017), their ability to track new climatically suitable areas was not experimentally tested.…”
Section: Resultsmentioning
confidence: 99%
“…Epiphytes' reliance on different water sources seems to be linked to their taxonomic affiliation; Liu et al . (2021) found that in a Chinese subtropical montane forest, bryophytes and ferns obtained water both from humus and fog, whereas lichens and seed plants relied almost exclusively on fog. Although significant tolerance to desiccation (Bader et al ., 2013) and temperature rise (up to an average of 3 °C) has been observed for some epiphytic species (Müller, Albach & Zotz, 2017), their ability to track new climatically suitable areas was not experimentally tested.…”
Section: Resultsmentioning
confidence: 99%
“…2016; Liu et al . 2021). Communities of vascular epiphytes (hereafter referred to as ‘epiphytes’), one of the most striking structural features of montane cloud forests, are expected to be particularly susceptible to drought as most epiphytes receive pulsed and atmospheric inputs of water (Gotsch et al .…”
Section: Introductionmentioning
confidence: 99%
“…Tropical montane cloud forests are one of the most vulnerable ecosystems to projected changes in the climate in terms of air warming, rising cloud bases, and frequent and severe droughts (Still et al 1999;Van Beusekom et al 2017;Bax et al 2021;Karger et al 2021), because many plants in these forests are more reliant on foliar water uptake, particularly epiphytes (Gotsch et al 2015;Eller et al 2016;Liu et al 2021). Communities of vascular epiphytes (hereafter referred to as 'epiphytes'), one of the most striking structural features of montane cloud forests, are expected to be particularly susceptible to drought as most epiphytes receive pulsed and atmospheric inputs of water (Gotsch et al 2015;Zotz 2016).…”
Section: Introductionmentioning
confidence: 99%